Factors Associated with an Increased Incidence of Complications in Patients with Hypertension - Marlizah, Marlizah; Faizal, Kgs. M.; Fitri, Nurwijaya (Inspirasi Foundation, 2026)
Introduction: Hypertension is a major global health problem and a leading cause of cardiovascular morbidity and premature mortality worldwide. The prevalence of hypertension continues to increase and is frequently associated with serious complications such as heart failure, stroke, kidney damage, and visual impairment. Several factors, including age, physical inactivity, and smoking habits, contribute to the development of hypertension-related complications. Understanding these associated factors is essential to strengthen preventive and promotive strategies in managing hypertension complications. Objective: Hypertension or high blood pressure is a serious medical condition that significantly increases the risk of heart disease, stroke, kidney disorders, and visual impairments. Data from 2024 show an increase in complications, with 70 cases related to heart failure and stroke, and 17 cases involving kidney damage and vision loss. Method: This study aims to identify the factors associated with the increased incidence of complications in hypertensive patients at Sejiran Setason Regional Public Hospital, West Bangka, in 2025. This research employs a quantitative method with a correlational analytic design and a cross-sectional approach, where independent and dependent variables are measured at a single point in time. Result: The results indicate a significant relationship between age, physical activity, and smoking habits with the occurrence of complications in hypertensive patients. Older individuals have a higher risk of hypertension-related complications. Additionally, a lack of physical activity and smoking habits further increase this risk. Conclusion: Based on these findings, preventive efforts are recommended through health lifestyle education and regular screening for high-risk groups. Further research is needed to evaluate the long-term effects of these factors on the progression of hypertension complications.